2017
DOI: 10.1186/s40494-017-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Artificial orpiment, a new pigment in Rembrandt’s palette

Abstract: This paper reports on how the application of macro X-ray fluorescence (MA-XRF) imaging, in combination with the re-examination of existing paint cross-sections, has led to the discovery of a new pigment in Rembrandt's palette: artificial orpiment. In the NWO Science4Arts 'ReVisRembrandt' project, novel chemical imaging techniques are being developed and applied to the study of Rembrandt's late paintings in order to help resolve outstanding questions and to gain a better understanding of his late enigmatic pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…4 Raman spectra of (a) the blue areas, (b) the green areas, (c) the dark blue areas and (d) the blue outline of the words in the cartouche in print A, B and C; and (e) dark blue, (f ) the light blue, and (g) the green in print D. Unless orpiment was foreseen, only the 1550-2600 cm −1 region of the Raman spectra was measured as characteristic contributions for both indigo and Prussian blue are found in this region. In Raman spectroscopy, the contributions observed between 100 and 600 cm −1 correspond to natural arsenic sulfide in prints by Hokusai (A-C) and to artificial arsenic sulfide in the print by Kunisada (D); the one at 1573 indicates indigo and the pair of contributions between 2095 and 2155 cm −1 correspond to Prussian blue profile and particular contributions are characteristic for the various bending and stretching bonds found in amorphous arsenic sulfide pigments, as reported in previous arsenic sulfide characterization studies [14,22,23]. While not previously reported as a characteristic for amorphous arsenic sulfide pigments, the increase in the 100-250 cm −1 region has consistently been noted in non-background corrected spectra in identification studies of amorphous arsenic sulfide pigments [8,10,14,20,22].…”
Section: Resultssupporting
confidence: 73%
“…4 Raman spectra of (a) the blue areas, (b) the green areas, (c) the dark blue areas and (d) the blue outline of the words in the cartouche in print A, B and C; and (e) dark blue, (f ) the light blue, and (g) the green in print D. Unless orpiment was foreseen, only the 1550-2600 cm −1 region of the Raman spectra was measured as characteristic contributions for both indigo and Prussian blue are found in this region. In Raman spectroscopy, the contributions observed between 100 and 600 cm −1 correspond to natural arsenic sulfide in prints by Hokusai (A-C) and to artificial arsenic sulfide in the print by Kunisada (D); the one at 1573 indicates indigo and the pair of contributions between 2095 and 2155 cm −1 correspond to Prussian blue profile and particular contributions are characteristic for the various bending and stretching bonds found in amorphous arsenic sulfide pigments, as reported in previous arsenic sulfide characterization studies [14,22,23]. While not previously reported as a characteristic for amorphous arsenic sulfide pigments, the increase in the 100-250 cm −1 region has consistently been noted in non-background corrected spectra in identification studies of amorphous arsenic sulfide pigments [8,10,14,20,22].…”
Section: Resultssupporting
confidence: 73%
“…2, 4). Palmierite has previously been identified as an alteration product in paint fragments from seventeenth-century Dutch paintings by Johannes Vermeer, Jacob Jordaens and Rembrandt, and the authors have also identified it in paintings by Jan Steen, Martinus Nellius and Jan Davidsz de Heem [20,[29][30][31][32][33]. Anglesite has previously been found on an ancient bronze inkwell and in paintings by Van Gogh and Memling [34][35][36].…”
Section: Alteration Products In Girl With a Pearl Earringmentioning
confidence: 99%
“…Its distribution cannot be associated to a specific color and it may be present as a transparent film. Indeed, various lead sulfatespalmierite but also anglesite (PbSO 4 ) and lanarkite [Pb 2 (SO 4 ) O]-have already been reported as degradation products in paintings, where they usually form a transparent film and sometimes protrusions (43)(44)(45)(46). They were detected in Old Master Paintings and associated with colored pigments (e.g., smalt and lakes) in combination with lead white that is present in the same or an adjacent paint layer.…”
Section: Resultsmentioning
confidence: 99%